Modern Nightstands Ttable Inspired by Stacking Furniture - Mohd Adzhar, Nur Anisah; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2021)
The recent development of housing has come with limited floor space that unable to accommodate various activities and other kinds of stuff, especially a big family. This leads to the spacing management problem among most small housing owners like low-cost apartments that brings uncomfortable and congested housing due to furniture, clothes, and other kinds of stuff. Therefore, this study will develop a stackable modern nightstand table to offer a solution for the aforementioned problem. This study starts with distributing the questionnaire to obtain data regarding the design criteria from target respondents. The design process will be done based on the criteria obtained from the questionnaire. The selected final design will be used to fabricate a prototype for this study. The questionnaire data indicated that most of the respondents’ keen on a nightstand with a drawer and built-in LED light. A pinewood and its original appearance are the most preferable finishing among the respondents. A prototype of a stackable modern nightstand table made from oriented strand board (OSB), pinewood and finished with wood colour. The outcomes from this study could provide better floor spacing management and facilitate more space for storage especially small items in the drawer.